Fundamental Science and Engineering Questions in Planetary Cave Exploration. Issue 11 (2nd November 2022) - Wynne, J. Judson; Titus, Timothy N.; Agha‐Mohammadi, Ali‐akbar; Azua‐Bustos, Armando; Boston, Penelope J.; de León, Pablo; Demirel‐Floyd, Cansu; De Waele, Jo; Jones, Heather; Malaska, Michael J.; Miller, Ana Z.; Sapers, Haley M.; et al.
Abstract: Nearly half a century ago, two papers postulated the likelihood of lunar lava tube caves using mathematical models. Today, armed with an array of orbiting and fly‐by satellites and survey instrumentation, we have now acquired cave data across our solar system—including the identification of potential cave entrances on the Moon, Mars, and at least nine other planetary bodies. These discoveries gave rise to the study of planetary caves. To help advance this field, we leveraged the expertise of an interdisciplinary group to identify a strategy to explore caves beyond Earth. Focusing primarily on astrobiology, the cave environment, geology, robotics, instrumentation, and human exploration, our goal was to produce a framework to guide this subdiscipline through at least the next decade. To do this, we first assembled a list of 198 science and engineering questions. Then, through a series of social surveys, 114 scientists and engineers winnowed down the list to the top 53 highest priority questions. This exercise resulted in identifying emerging and crucial research areas that require robust development to ultimately support a robotic mission to a planetary cave—principally the Moon and/or Mars. With the necessary financial investment and institutional support, the research and technological development required to achieve these necessary advancements over the next decade are attainable. Subsequently, we will be positioned to robotically examine lunar caves and search for evidence of life within Martian caves; in turn, this will set the stage for human exploration and potential habitation of both the lunar and Martian subsurface. Plain Language Summary: We have now acquired cave data across our solar system—including the identification of potential cave entrances on the Moon, Mars, and at least nine other planetary bodies. These discoveries gave rise to the study of planetary caves. To help advance this field, we conducted an expert‐opinion based social survey to identify a strategy to explore caves beyond Earth. We focused primarily on astrobiology, the cave environment, geology, robotics, instrumentation, and human exploration. First, we assembled a list of 198 science and engineering questions. Then, through a series of social surveys, 114 scientists and engineers winnowed down the list to the top 53 highest priority questions. This exercise resulted in identifying emerging and crucial research areas that require robust development to ultimately support a robotic mission to a planetary cave—principally the Moon and/or Mars. With the necessary financial investment and institutional support, the research and technological development required to achieve these necessary advancements over the next decade are attainable. Subsequently, we will be positioned to robotically examine lunar caves and search for evidence of life within Martian caves; in turn, this will set the stage for human exploration and potential habitation of both the lunar and Martian subsurface. Key Points: Robotics and instrument advancements identified as linchpin focal areas for in situ study of planetary caves Research and technological development required for lunar and/or Martian cave exploration is achievable in next decade with proper investment First application of systematic and statistically rigorous social survey to identify science and engineering requirements in planetary science